Nuclear Factor-Kappa B Activity Regulates Brain Expression of P-Glycoprotein in the Kainic Acid-Induced Seizure Rats - Nian Yu; Qing Di; Hao Liu; Yong Hu; Ying Jiang; Yu-kui Yan; Yan-fang Zhang; Ying-dong Zhang (Mediators of Inflammation)
This study was aimed to investigate the effect of NF-κB activity on the seizure susceptibility, brain damage, and P-gp expression in kainic acid- (KA-) induced seizure rats. Male SD rats were divided into saline control group (NS group), KA induced epilepsy group (EP group), and epilepsy group intervened with NF-κB inhibitor-pyrrolidine dithiocarbamate salt (PDTC group) or with dexamethasone (DEX group). No seizures were observed in the rats of NS group. Compared with NS group, increased P-gp expression and NF-κB activation in the rat brain of the EP group were observed after KA micro-injection. Both PDTC and DEX pre-treatment significantly increased the latency to grade III or V seizure onset compared to EP group but failed to show neuron-protective effect as the number of survival neurons didn't significantly differ from that in EP group. Furthermore, PDTC pre-treatment significantly decreased P-gp expression along with NF-κB activation in the hippocampus CA3 area and amygdala complex of rats compared with the EP group, implying that NF-κB activation involved in the seizure susceptibility and seizure induced brain P-gp over-expression. Additionally, DEX pre-treatment only decreased P-gp expression level without inhibition of NF-κB activation, suggesting NF-κB independent pathway may also participate in regulating seizure induced P-gp over-expression.